Seismic signals generated at a water-ice interface from smoothed particle hydrodynamical simulations - Ross Turner; Anya Reading (2021)
Instrument advances and international field programs have expanded the availability of recordings that contain records of seismic disturbances generated by glacier processes. Some of these processes, such as basal slip and crevasse propagation, have mechanisms with plate tectonic deformation counterparts, however, many glacier signals are generated by moving meltwater. A need exists, therefore, to better understand the seismic response of moving water on glaciers. We present a computational framework for the simulation of seismic signals at the interface between moving water and ice, assuming that the recording station is located on the glacier of interest. We illustrate the capability of the simulation framework with examples based on supraglacial melt flow: the breaking of a melt-water lake dam, and the flow of melt water around right-angle and other more gently curved bends. The framework is flexible, allowing seismic signals to be generated for water flows in arbitrary geometries with one or more obstacles disrupting the flow. We find that the modelling framework enables complexity, such as multiple arrivals, from seismic signals from moving meltwater to be better understood. We make the code available as an open source resource for the glacier geophysics community. Knowledge gained should inform the improved interpretation of signals, and detection of process change over time, for active glaciers remote from habitation. Better understanding the character of seismic signals resulting from a variety of water-ice interactions will thus support future monitoring of these intermittent processes in glaciers such as those that drain the great ice sheets of Antarctica.